Anticancer Activity of New Synthetic α‐Methylene‐δ‐Lactones on Two Breast Cancer Cell Lines. (18th September 2013) - Wyrębska, Anna; Gach, Katarzyna; Lewandowska, Urszula; Szewczyk, Karolina; Hrabec, Elżbieta; Modranka, Jakub; Jakubowski, Rafał; Janecki, Tomasz; Szymański, Jacek; Janecka, Anna
Abstract Natural products are important leads in drug discovery. The search for effective plant‐derived anticancer agents or their synthetic analogues has continued to be of interest to biologists and chemists for a long time. In this report, cytotoxicity and anticancer activity of new synthetic α‐methylene‐δ‐lactones was tested against two breast cancer cell lines, invasive, hormone‐independent MDA‐MB‐231 and hormone‐dependent MCF‐7. Cytotoxicity was examined using MTT assay. The ability to induce apoptosis and changes in mitochondrial membrane potential was studied by flow cytometry. The expression levels of pro‐ and anti‐apoptotic genes were determined by quantitative real‐time PCR. Cancer cell migration and invasion were assessed by wound healing and Matrigel assays. Additionally, secretion of proteins associated with invasiveness, metalloproteinase‐9 (MMP‐9) and urokinase plasminogen activator (uPA) was investigated using commercial ELISA kits and MMP‐9 activity by gelatin zymography. A natural sesquiterpene lactone, parthenolide, was used as a positive control. Screening results showed all four analogues to be highly cytotoxic. The most potent compound of the series, 1‐isopropyl‐2‐methylene‐1, 2‐dihydrobenzochromen‐3‐one, designated DL‐3, which reduced the number of viable MDA‐MB‐231 and MCF‐7 cells with the IC50 values of 5.3 μM and 3.54 μM, respectively, was selected for further research. DL‐3 activated the intrinsic pathway of apoptosis, associated with the loss of mitochondrial membrane potential and changes in Bax/Bcl‐2 ratio. DL‐3 also inhibited the movement of both types of breast cancer cells. Suppression of cell migration and invasion was the result of the decreased secretion of enzymes responsible for the degradation of the extracellular matrix, MMP‐9 and uPA. These findings show that the synthetic α‐methylene‐δ‐lactone, DL‐3, displays potential to be further explored in the development of new anticancer agents.